Osteological development and homology of the prenasal bones in the neotropical toad Rhinella fernandezae (Anura: Bufonidae) - Alcalde, Leandro (2017)
Bufonid toads of the Rhinella granulosa species group are reported to have paired prenasal bones typically absent in other bufonids. The homology of the prenasal bone is explored throughout ontogeny herein by studying larvae, froglets, and adult R. fernandezae. I found that these putative bones are actually part of the enlarged and exposed anterior ends of the septomaxillae. An unpaired prenasal bone not previously described for other toads was found at the anterior end of the snout of R. fernandezae. Its position, origin, and shape indicate this bone is a homologue with the prenasal described for some casque-headed hylids.